Rethinking Moral Agency: Luciano Floridi and the Ethics of AI in the Age of ChatGPT - Sabu, Fransiskus Xaverius; Asmiyanto, Taufik (Program Studi Ilmu Perpustakaan UIN Alauddin, 2026)
Background: As Artificial Intelligence (AI) becomes increasingly pervasive, the technology must be viewed as more than a mere utility for task automation. To preserve human agency, AI integration should facilitate freedom of expression and prevent the systematic marginalization of human roles within the digital ecosystem. Purpose: This study provides a critical elaboration of Luciano Floridi’s Ethics of Information (EOI). The researchers aim to uncover the philosophical essence of Floridi’s thought regarding artificial agents and their moral status within the